Utilização de madeira residual de pinus na adsorção de chumbo e posterior gaseificação e geração de energia elétrica - Antonelli, Jhonatas (2015)
The search for comfort and welfare resulted in an increase in industrial production, consumption of fuel and energy. With this new problems arose, such as the generation of contaminated effluent, and the need to obtain new energy sources. Biomass is one of the most promising energy sources and abundant in the environment and can replace fossil fuels, plus the ability to use it in the treatment of contaminated effluents. This study evaluated the ability of residual pinewood in the lead adsorption and the generation of synthesis gas. In the adsorption process Lead (Pb) was evaluated the pH, the kinetics of the adsorption process and the rate of removal in 72 hours. In the gasification process was measured by the consumption of wood gasifier, gasifier efficiency, gas consumption and the efficiency of the motor generator, the chemical composition of the synthesis gas and the amount of lead present in the ash and gas. In tests conducted in the laboratory the ideal pH for the solution pH 4, reaching removal rate of 96.15% and breakeven point at 180 min. In pilot scale removal of Pb retention after 72 hours was 96%. The gas output of the gasifier and the gas engine by consumption were measured using a gasometer in which the average gas production was 11.09 m³ hˉ¹ and the average consumption of wood hˉ¹ 5.48 kg, with a yield of 2.03 m3 kgˉ¹ and average efficiency of the gasification 52.3%. For tests with the motor-generator, the best condition for the load was 2.0 kW, where the gas consumption per kW produced reached 4.86 m³ kWˉ¹ with 14.81% efficiency. The gas analysis showed an average concentration of 14.85% H2, 30.1% and 50.49% CO2 in atmospheric air. The concentration of Pb in the gas was well below the limit established by law and the concentration of Pb in the ashes was 2,646 g kg-1.